The Roman Altar Dedicated to Zeus from Velico Târnovo – Bulgaria: Reconsidered - Ovadiah, Asher (Gerión. Revista de Historia Antigua, 2012)
This Roman altar, dedicated to Zeus, was found among the ruins of a Roman civil building of the Late Empire, near the Ottoman Firuz Bey Mosque on the Carévéc hill in Velico Târnovo, Bulgaria. It is dated to the second-third century CE. The relief depicted on the altar is a sophisticated combination of a stylized and schematic thunderbolt and ant. Both are forming one entity with a dual significance and associated from the mythological point of view with Zeus.